Catechesis for the new evangelization : Vatican II, John Paul II, and the unity of revelation and experience - Pedraza, Brian (The Catholic University of America Press, 2020)
"Examines the theological foundations of catechesis in the Catholic Church's understanding of divine revelation and its reception by the human person as expressed in the constitutions of Vatican II (Dei Verbum and Gaudium et Spes), using this as a background to explore the anthropology of Pope John Paul II and its applicability to the development of the New Evangelization emphasized by Popes John Paul II, Benedict XVI, and Francis"--